ANALYSIS OF DIGITAL ERA HUMAN RESOURCE RECRUITMENT AT THE AL-MANAAR ISLAMIC BOARDING SCHOOL IN BATUHAMPAR - Alkaf, Radtria; Ulmadevi, Ulmadevi; Sesmiarni, Zulfani; Zakir, Supratman; Simbolon , Ali Mustopa Yakub (Idaarah: Jurnal Manajemen Pendidikan, 2023)
Al-Manaar Batuhampar Islamic Boarding School is a private educational institution that has been established since 1943. However, since its establishment, the boarding school has never conducted formal recruitment processes, except in 2022 due to an increased number of students, requiring a larger workforce. The aim of this research is to understand the human resource recruitment process at Al-Manaar Batuhampar Islamic Boarding School in the current digital era. The research method used is qualitative descriptive. Data collection was done through interviews and analyzed using the data analysis method proposed by Miles and Huberman (1994), which includes data reduction, data presentation, and drawing conclusions. In this study, the author found that Al-Manaar Batuhampar Islamic Boarding School does not use appropriate methods in recruiting human resources and has not fully utilized technology. Only one interview is conducted without any follow-up interviews, and no written tests are conducted before accepting prospective human resources. Additionally, some recruitment processes are still done manually. From the results of this research, it can be concluded that the human resource recruitment process at Al-Manaar Batuhampar Islamic Boarding School is not in line with the recruitment steps proposed by experts.